ETHICAL IMPLICATIONS OF CARE OF THE SELF IN THE WORK OF MICHEL FOUCAULT - Messias, Elvis Rezende; Santos, Iuri de Carvalho (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
This text is the result of bibliographical research and theoretical-conceptual perspective and problematizes how the ethical issue is present in the work of Michel Foucault. The general objective of the article is to understand the ethical implications of self-care in light of Foucault's work. Initially, the text investigates when and how ethical reflection is found in Foucault's thought. Subsequently, it identifies the ethical relationship with oneself and its postulates. Finally, it seeks to elucidate how Foucault finds in the ethics of self-care a way of constructing oneself, a relationship distinct from subjection to norms, its characteristics and also the model of the aesthetics of existence for an elaboration of life as a work of art. in a new way of being.